1978
DOI: 10.1007/bf02669917
|View full text |Cite
|
Sign up to set email alerts
|

Study of the accelerated oxidation of low and high erucic rapeseed oil

Abstract: High ABSTRACTThe oxidation of a low erucic rapeseed oil was compared to the oxidation of a high erucic rapeseed oil in the temperature range 100 to 140 C. The two oils were found to be very similar in the rate of peroxidation, viscosity increase, change of refractive index, oxidation of the individual fatty acids, and hydroperoxide decay. Rate constants and activation energies for the change of these quantities were determined. The rate of hydroperoxide decomposition was found to be of first order for both oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Use of purge and trap sampling of volatiles from plant tissues has previously been done for bell peppers (Luning et al, 1994), broccoli (Forney et al, 1991), tomatoes (Buttery and Ling, 1993), and muskmelons (Yabumoto et al, 1978). Flushing samples with oxygen or air to induce oxidative changes has been reported for rapeseed oil by Erkilla et al (1978) and for soybean oil by Warner and Mounts (1984).…”
Section: Introductionmentioning
confidence: 99%
“…Use of purge and trap sampling of volatiles from plant tissues has previously been done for bell peppers (Luning et al, 1994), broccoli (Forney et al, 1991), tomatoes (Buttery and Ling, 1993), and muskmelons (Yabumoto et al, 1978). Flushing samples with oxygen or air to induce oxidative changes has been reported for rapeseed oil by Erkilla et al (1978) and for soybean oil by Warner and Mounts (1984).…”
Section: Introductionmentioning
confidence: 99%
“…endpoints for L E A R and corn oil were 95 and 225 meq/kg, respectively. Erkilla (13) found that L E A R had a PV above 50 at the end of the AOM induction period as determined by refractive index measurements. Based on reports in the literature on flavor data and PV, the levels of deteriora-1presented at the annual meeting of the Canadian Section of AOCS, held in October 1987 in Winnipeg, Manitoba, Canada.…”
mentioning
confidence: 98%
“…Increased SFO production in the U.S., and approval of L E A R for food use by the Food and Drug Administration in 1985 (3), has generated interest in the use of SFO and L E A R for salad and cooking oils and as ingredients in formulated foods. Previous research on the oxidative stability of SBO (4-7), SFO (8)(9)(10) and L E A R (11)(12)(13)(14) has been reported, although few studies on the flavor evaluation of autoxidized L E A R are in the literature. Several researchers have evaluated the stability of vegetable oils by the active oxygen method (A.O.M.)…”
mentioning
confidence: 99%
“…Depending on whether hydrogen bonds stabilize a cage mechanism (see Ref. [23]) or not, their decompositions are considered either unimolecular [24][25][26][27][28][29][30][31][32][33][34][35] or bimolecular [31,33,35,36]. The molecularity of the decomposition remains an open question (see the discussion in Ref.…”
Section: Principlesmentioning
confidence: 99%